Cultural Factors of Shipwreck Site Formation: An Examination of Ferrous Shipwrecks on the Outer Banks - Bera, Daniel J. (East Carolina University)
This thesis proposes a course of research to examine the influence human decision-making processes (cultural factors) have on our understanding of site formation processes and the management of ferrous shipwrecks. Two shipwrecks found off the coast of North Carolina, the late-19th century iron sloop-of-war USS Huron and the early-20th century steel oil tanker Paraguay will serve as case studies for comparative purposes. This study utilized primary and secondary historical documents to inventory the cultural factors involved in the construction, use life, and deposition of each vessel. Subsequently, inspection of these shipwrecks collected information regarding their current state of preservation via qualitative and quantitative analysis of non-cultural site formation processes. Qualitative methods involved the comparison of ships and shipwrecks through historical records and the formation of interpretations of the transformation processes. Quantitative methods involved the collection of corrosion variables. By interpreting present-day site status through the lens of site formation theory, the role of human decision-making processes (pre- and post-wrecking) as both playing a role in the state of preservation of USS Huron and Paraguay and also influencing future site management is assessed.
Keywords: Archaeology; Maritime archaeology; Maritime history; Maritime studies; Shipwrecks--North Carolina; Ships, Iron and steel; Ships--Conservation and restoration; Underwater archaeology